2021 Crisis Preparedness Training: Annual Report. Issue 12 (17th December 2021) - Johnson, Julia; Vincent, Andrew
Abstract: The European Food Safety Authority (EFSA) undertook two crisis training activities during 2021. Both were facilitated online and based on the fictional scenario of a Rift Valley Fever (RVF) outbreak in the European Union (EU). An External Crisis Preparedness Training (ECPT) workshop occurred in July 2021, targeting participants from EU Member States (MSs), EU Agencies and international animal/human health organisations. It was jointly devised, developed and delivered by EFSA with the Istituto Zooprofilattico Sperimentale dell' Abruzzo e del Molise (IZSAM), and has been reported in EFSA Supporting Publications (IZSAM & Instinctif Partners Ltd., 2021). The second workshop, described in this document and designated the Internal Crisis Preparedness Training (ICPT), occurred in November 2021. Using a repurposed version of the ECPT's RVF scenario, the ICPT's overall training objective was to plan and practise EFSA's management of risk communication, in conjunction with other European agencies, during a joint urgent response to a multi‐country animal health/public health outbreak. Fourteen participants from EFSA, EFSA's Communications Expert Network (CEN) and the European Centre for Disease Prevention and Control (ECDC) attended the training, plus 13 observers from EFSA and the European Commission's (EC's) Directorate‐General for Health and Food Safety (DG SANTE). Plenary and working group activities extended across 1 day, including 3 presentations on EFSA's and ECDC's remits, capabilities and communications best practice. A scenario exercise explored how EU agencies and DG SANTE would respond and collaborate if RVF entered the EU. The fictional scenario's 3 escalating outbreak phases spanned several weeks, encompassing infection spread amongst animal and human populations within several MSs and an EU candidate country. Plenary debrief sessions distilled both events' discussions into practical recommendations for future enhancements and improvements in areas of collaboration, process and communication. The objectives of each event were achieved, based on recorded outcomes and evaluative feedback from participants.